A tensão entre democracia e participação nos governos de esquerda : os casos do Brasil, Chile e Venezuela - Fukushima, Kátia Alves (2016)
This study aims to examine whether there was progress of leftist governments, specifically, the Lula government in Brazil (2003-2010), Chavez in Venezuela (1999-2013) and Bachelet in Chile (2006-2010) in the conformation a model of participatory democracy. The theoretical basis of the present research is the work of Macpherson (1977) "The Life and Times of Liberal Democracy" that comprises liberal democracy and participatory democracy as complementary terms, as the passage from one to another occurs through the composition, and not by denial. According to this theoretical approach, participatory democracy is understood as the improvement of liberal democracy, assuming an active and less unequal society, in which the citizen has opportunities to develop their skills and participate more and more of the decision process. Therefore, analysis will be performed compared from two dimensions: a) the correlation of political and economic forces in each country (with the opposition parties, business sectors, media and sectors of the church) and; b) the asymmetry of political resources (coming from the institutional legacies, the political system, the pacts and social support base). When comparing the three leftist governments from these two dimensions, we observe the configuration of a "government breaks" (Chavez government in Venezuela), a "moderate government" (Lula government in Brazil) and a "continuity of government" (first mandate Bachelet in Chile). The specific objective was to assess whether these differences between left governments affected in the process of implementation mechanisms for participation in their democracies. Thus, it appears - from three areas – 1) mechanisms of participation and inclusion, 2) favorable conditions for participation, and 3) citizen participation – that among the cases analyzed there is significant variation in the degree of implementation participatory mechanisms and how these governments have devised participation. The conclusions drawn from the data on participation showed that the "government of continuities" Bachelet remained closer to the "balance of democracy" in which popular sovereignty is restricted to the electoral arena as the "government breaks" Chavez approached more participatory democracy. However, the "moderate government" Lula positioned at an intermediate point between the two cases.